Oxidative Modification of the Proteins of Breast and Cow Milk - E. Vysokogorskiy, Valeriy; A. Sokolova, Mariya; V. Strelchik, Natalya; N. Lazareva , Oksana; V. Antonov, Oleg (KnE Life Sciences, 2021)
One of the important modern characteristics of the nutritional and biological value of milk and dairy products is the antioxidant properties. The high stability and sensitivity of the determination of carbonyl derivatives of proteins, as well as the informative value of the action of antioxidants, allow using them as the markers of oxidative damage. The purpose of this paper was to compare the level of carbonyl derivatives of proteins in breast and cow milk. The determination of the oxidative modification of proteins was based on the reaction of carbonyl derivatives of amino acid residues with 2, 4-dinitrophenylhydrazine. The content of the products was determined during spontaneous and metal-catalyzed oxidative modification of the proteins. During the determination of the spontaneously formed carbonyl derivatives of the proteins, their significantly higher content in cow milk compared to breast milk was established. This increase ranged from 46% to 83% at different wavelengths. Thus, the determination of carbonyl derivatives of amino acid residues of the proteins made it possible to reveal significant differences in the antioxidant properties of breast and cow milk, manifested in a lower level of carbonyl derivatives in breast milk. The lower level of carbonyl derivatives in the composition of breast milk proteins is likely associated with the increased activity of the antioxidant system of breast milk or the increased rate of removal of damaged proteins upon activation of milk proteases. Keywords: carbonyl derivatives, oxidative modification, proteins, human milk, breast milk, metal-catalyzed